Sinergi Konsep Dzikir Al-Ghazali Dan Cognitive Behavior Therapy Aaron T. Beck Untuk Penyembuhan Emosional Pasien Skizofrenia - Putri Amalia Rizky (Abdurrauf Journal of Education and Islamic Studies, 2026)
Schizophrenia is a chronic mental disorder characterized by persistent cognitive distortion and emotional instability. Although pharmacological treatment effectively reduces positive symptoms such as hallucinations and delusions, emotional recovery particularly negative symptoms including flat affect, anhedonia, and impaired emotional regulation remains a significant challenge. Cognitive Behavior Therapy (CBT) developed by Aaron T. Beck has demonstrated effectiveness in symptom management and social functioning improvement. However, this approach primarily emphasizes cognitive-behavioral aspects without integrating spiritual dimensions that are meaningful for Muslim patients. This study aims to explore the synergy between Al-Ghazali’s concept of dhikr and Cognitive Behavior Therapy in supporting emotional healing among schizophrenia patients. The research employs a qualitative library research approach using conceptual-comparative analysis of classical and contemporary literature. The findings indicate that integrating dhikr with CBT has the potential to strengthen emotional regulation, facilitate cognitive restructuring, and enhance psychological resilience. This synergy contributes to the development of a holistic psychospiritual therapeutic model that combines Islamic spiritual heritage with modern psychotherapy principles. [Skizofrenia merupakan gangguan mental kronis yang ditandai oleh distorsi kognitif dan ketidakstabilan emosional yang persisten. Meskipun terapi farmakologis efektif dalam menurunkan gejala positif seperti halusinasi dan waham, pemulihan emosional khususnya terkait gejala negatif seperti afek datar, anhedonia, dan gangguan regulasi emosi masih menjadi tantangan signifikan dalam praktik kesehatan mental. Cognitive Behavior Therapy (CBT) yang dikembangkan oleh Aaron T. Beck terbukti membantu pengelolaan gejala dan peningkatan fungsi sosial, namun pendekatan ini umumnya berfokus pada aspek kognitif-perilaku tanpa mengintegrasikan dimensi spiritual yang penting bagi pasien Muslim. Penelitian ini bertujuan mengeksplorasi sinergi konsep dzikir Al-Ghazali dengan CBT dalam mendukung penyembuhan emosional pasien skizofrenia. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kepustakaan dan analisis komparatif-konseptual terhadap literatur klasik dan modern. Hasil kajian menunjukkan bahwa integrasi dzikir dan CBT berpotensi memperkuat regulasi emosi, mendukung restrukturisasi kognitif, serta meningkatkan ketahanan psikologis pasien. Sinergi ini berkontribusi pada pengembangan model terapi psikospiritual yang memadukan warisan spiritual Islam dengan prinsip psikoterapi modern.]